Protocols for extraction and purification of rutin from leafy by-products of asparagus (Asparagus officinalis) and characterization of the purified product - Chitrakar, Bimal; Hou, Yakun; Devahastin, Sakamon; Zhang, Min; Sang, Yaxin (Food chemistry, 2023)
[Display omitted] •Asparagus leafy by-products was explored as a cheap rutin source.•Extraction was done using the best extraction yield.•Purification of the crude extract through a newly proposed method.•The proposed method was able to give pure rutin crystals.•The purification yield and the purity of rutin was high. Valorization of asparagus leafy by-products as a potential source of rutin through selected extraction and purification protocols was investigated. Protocol resulting in the highest extraction yield was first selected. Crude extract was subject to purification via multiple liquid–liquid back extraction using ethanol, methanol or water as a solvent; selection of the most appropriate purification solvent was made based on rutin solubility. The proposed purification protocol yielded yellow-color crystals, which were characterized by fluorescence microscopy, Fourier-transform infrared spectroscopy and liquid chromatography-mass spectrometry to confirm them as rutin. Purity of rutin was confirmed by ultra-performance liquid chromatography at 97.6%; yield of the purified rutin was determined to be 78.2%. The remaining rutin (21.8%) was found in the liquids collected at various stages of purification; such liquids could be recycled using the same purification process. The proposed protocols are simple, yet effective for rutin extraction and purification from asparagus leafy by-products.